Blue light emitting fluorophore for the effective detection of cyanide ion and electronic test kit development for real time measurement. (February 2023) - Manivannan, Ramalingam; Son, Young-A
Abstract: This work deals with the blue light emitting fluorophore containing indolium/coumarin fused conjugated system probe JE5, for the effective detection of cyanide ion. The probe holding diethylamino coumarin unit as a donor unit and indolium as an acceptor unit that is connected by a π-conjugation. The cyanide ion sensing ability of the probe has been monitored by UV–visible and fluorescence measurement. The probe exhibits a vivid color change from deep blue to pale yellow before and after sensing cyanide ion. The color change confirmed by visual and UV–visible titration studies. Fluorescence enhancement was observed for the probe after cyanide addition. The obtained color change was due to the disconnection of ICT between the donor and acceptor unit resulting in color change with the added cyanide ion. The limit of detection of the probe JE5 found to be 1.99 μM and 0.97 nM by UV–Visible and fluorescence methods. Electronic device with proper coding data developed for the effective detection of cyanide ion. The stoichiometry of 1:1 binding between JE5 and cyanide ion was obtained. Graphical abstract: Image 1 Highlights: Blue light emitting fluorophore-indolium/coumarin fused probe developed. The probe exhibits a vivid color change from deep blue to pale yellow up on cyanide detection. Easy to handle electronic test kit developed for the effective detection of cyanide ions in real samples.